Dasatinib-Induced Pulmonary Arterial Hypertension Treated with Upfront Combination Therapy - Makoto Nishimori; Tomoyuki Honjo; Kenji Kaihotsu; Naohiko Sone; Sachiko Yoshikawa; Junichi Imanishi; Kazuhiko Nakayama; Noriaki Emoto; Masanori Iwahashi (Case Reports in Cardiology)
Pulmonary arterial hypertension (PAH) is a rare complication of dasatinib that was approved as a first-line therapy for chronic myelocytic leukemia (CML). A 24-year-old man presenting dyspnea at rest and leg edema was admitted to our hospital. He had been diagnosed with CML and prescribed dasatinib for 4 years. Chest X-ray showed significant bilateral pleural effusion and heart enlargement. Echocardiography revealed interventricular septal compression and elevated peak tricuspid regurgitation pressure gradient of 66.7 mmHg indicating severe pulmonary hypertension. After the other specific diseases to provoke PAH were excluded, he was diagnosed with dasatinib-induced PAH. Despite discontinuation of dasatinib and intravenous administration of diuretic for two weeks, World Health Organization (WHO) functional class was still II and mean pulmonary arterial pressure (PAP) was high at 37 mmHg. Therefore, we administered sildenafil and bosentan together as an upfront combination therapy three weeks after dasatinib discontinuation. Six months later, his symptoms improved to WHO functional class I and mean PAP was decreased to 31 mmHg. Although PAH is a rare complication of dasatinib, symptomatic patients prescribed with dasatinib should have an echocardiogram for PAH screening. Moreover, the upfront combination therapy would be a useful option for symptomatic patients after discontinuation of dasatinib.